2019
DOI: 10.1007/s00209-019-02354-1
|View full text |Cite
|
Sign up to set email alerts
|

Donovan’s conjecture, blocks with abelian defect groups and discrete valuation rings

Abstract: We give a reduction to quasisimple groups for Donovan's conjecture for blocks with abelian defect groups defined with respect to a suitable discrete valuation ring O. Consequences are that Donovan's conjecture holds for O-blocks with abelian defect groups for the prime two, and that, using recent work of Farrell and Kessar, for arbitrary primes Donovan's conjecture for O-blocks with abelian defect groups reduces to bounding the Cartan invariants of blocks of quasisimple groups in terms of the defect.A result o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2
1

Relationship

5
3

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…contradicting the minimality of G. A similar argument using Theorem 1.2 shows the bound on strong O-Frobenius numbers. We have shown that the Cartan invariants and the strong O-Frobenius numbers of all blocks with defect group isomorphic to P are bounded, and so the result follows by [14,Corollary 3.11]. ✷…”
mentioning
confidence: 85%
See 2 more Smart Citations
“…contradicting the minimality of G. A similar argument using Theorem 1.2 shows the bound on strong O-Frobenius numbers. We have shown that the Cartan invariants and the strong O-Frobenius numbers of all blocks with defect group isomorphic to P are bounded, and so the result follows by [14,Corollary 3.11]. ✷…”
mentioning
confidence: 85%
“…In [21] Kessar showed that the k-Donovan conjecture is equivalent to showing Conjecture 1.1 and that the Morita Frobenius number (defined in §2) of a block is bounded in terms of the order of the defect groups. Variations on the Morita Frobenius number for blocks defined over O were given in [13], including the strong O-Frobenius number sf O (B), and in [14] the analogue of Kessar's result was shown for blocks defined over O. In [11] Düvel reduced Conjecture 1.1 to quasisimple groups (although the result in [11] is not quite strong enough for our purposes as stated).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…This is particularly important since Külshammer [13] showed that Picard groups play an important role in both Donovan's conjecture and the classification of blocks of a given defect group. This theme is explored in [6,7]. In the way of actual computations, [11] determines the Picard group of the principal block of A 6 for p D 3, [8] determines Picard groups of almost all blocks of abelian 2-defect of rank three, and this will certainly not mark the end of the story.…”
Section: Introductionmentioning
confidence: 99%
“…This is particularly important since Külshammer [Kül95] showed that Picard groups play an important role in both Donovan's conjecture and the classification of blocks of a given defect group. This theme is explored in [Eat16,EEL19]. In the way of actual computations, [HN04] determines the Picard group of the principal block of A 6 for p = 3, [EL18] determines Picard groups of almost all blocks of abelian 2-defect of rank three, and this will certainly not mark the end of the story.…”
mentioning
confidence: 99%